Legal Certainty Special Mining Business License (Study: IUPK as a Continuation of Contract of Work and Work Agreement for Coal Mining Exploitation in the Minerba Law) - Riyadi, Panji (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
After the promulgation of Law Number 3 of 2020 many people highlighted the addition of Article  169A which explains the guarantee of extension through special mining business license (IUPK) for holders of the contract of work (KK) and work agreement for coal mining exploitation (PKP2B) which will expire. However on the other hand this Article also creates unrest for KK and PKP2B holders because the granting of extensions through the IUPK is not automatically granted but with considerations that have been explained in the law. The formulation of the problem raised in this study is about the legal certainty of granting IUPK and legal protection for KK and PKP2B holders if the application for extension through IUPK is rejected by the Ministry of Energy and Mineral Resources. This study uses a normative juridical research method namely through a literature study with a statutory approach. The results indicate that there was no legal certainty from the IUPK as a Continuation of Contract/Agreement Operations and no legal protection for  KK  and  PKP2B  holders if the extension through IUPK is rejected by the relevant Minister. The provisions regarding  these  rules  in  the  current  Minerba  Law  must  be  explained  more  clearly  in  the  Government  Regulation  regarding  Minerba  in  order  to  provide  legal  certainty  and  protection  for  mining  business actors.